An Investigation of Students’ Reading Habits and Vocabulary Mastery - Merlin Olviani Devi Poluan; Virginia Gabrella Sengkey (Journal of English Language and Education, 2026)
This study sought to describe and determine the correlation between students’ reading habits and their vocabulary mastery among eleventh-grade students at a private high school in North Sulawesi. The research design was descriptive-correlative method using Mean score and Pearson-product moment correlation coefficient. There were 92 respondents who participated in this study. The instruments were 23 items questionnaire on reading habits and 39 objective questions of vocabulary test. The findings of this research were: (a) the type of reading most frequently read was the Bible, and there was a relatively small number of students who are interested in reading; (b) the level of students’ reading habits was moderate; (c) the level of students’ vocabulary mastery was low; (d) there was no significant correlation between students’ reading habits and their vocabulary mastery (p=0.093, r=0.176). This study recommends that: (a) the other types of books should be read, and the reading interest increased; (b) the moderate level of reading habits should be kept up and even improved; (c) the other factors for improving vocabulary mastery should be identified.